Gender Differences in Multi-Employee Gift Exchange with Self-Reported Contribution - Grimm, Veronika; Rau, Holger; Schächtele, Simeon (2019)

On gender-specific behavior in collective bargaining - Buschmann, Benjamin; Grimm, Veronika; Rau, Holger; Stephan, Gesine (2019)

On the impact of quotas and decision rules in collective bargaining - Feicht, Robert; Grimm, Veronika; Rau, Holger; Stephan, Gesine (European Economic Review, 2017)
We conduct a novel type of multi-person one-shot game that reflects important aspects of collective bargaining. In all treatments a proposer has to divide a pie among herself and two groups of three recipients each. She cannot discriminate within, but across groups. A committee with representatives from one or both groups takes acceptance decisions. In a 2 × 2 design we vary (i) representation in the decision committee (one vs. both groups) and (ii) the decision rule (unanimity vs. majority voting). We find that (i) representation of a group in the committee is crucial for receiving a significant share, (ii) proposals are balanced only if both groups have veto power, (iii) negotiations often fail if the decision environment gives insufficient guidance on what an appropriate proposal is, and (iv) non-binding communication substantially reduces rejection rates and proposer share